Jurisdição constitucional e a efetividade do direito fundamental a igualdade - Silva, Diego Ramirez Grigio (2009)
The present dissertation has the purpose of analyzing the exercise of the constitutional jurisdiction over the perspective of the fundamental right’s effectivety for the equality. The used method will be the dialectic, specific from the social science and which understands the historic reality, not only as a flow, but, mostly, as the Genesis of an explanation. The applied technique for the data collection is going to be the consultation of national and foreign works, plus scientific articles and Law decisions. Getting into the proposed theme, we identify the constitutional jurisdiction as instance of nonmajoritarian power, which the aim is to control and annul the acts of the other functions referred to the State (legislative or executive) opposed to the constitutional rules, avoiding the abuse of irresponsible majorities. As the central problem of our work, we punctuate the exam over the contribution of the constitutional jurisdiction in the effectuation of the fundamental right for equality. Therefore, we chose some elements about the evolution of the Constitution, State, and fundamental rights, emphasizing the present moment of the constitutionalism and the mainly changes made in the contemporary constitutional right, focusing on the aggravation of the Constitution’s normative strength, the rising of principles and its new constitutional interpretation and the revigoration of the constitutional jurisdiction as well. Considering the methodologic cutting, we broached some aspects that surround the constitutional jurisdiction study, history landmark, (especially in the USA and in Brazil), principal models, systematization of the Brazilian Constitutional Jurisdiction and its relation with the Democratic State and with the fundamental rights, where we emphasize the fundamental right for the equality. We concluded, in the end, that the political and social reshape of the contitutional jurisdiction, construted in the 2º post-war and forged in the Brazilian Constitution of 1988, added to the unwilling social unequality and to the deficit of public politic of the equality’s promotion, induce a significant raise of the contribuition of the jurisdiction function in the fundamental right’s effectivety for the equality.